Effects of Cu and Zn coated urea on rice production in acidic and alkaline soils - Babar, Saima Kalsoom (2016)
Acidic soils of Malaysia and alkaline soils of Pakistan are in incidence of micronutrient insufficiency. Despite of that urea is considered as the most broadly used nitrogen (N) fertilizer. Unfortunately, its application is associated with losses such as emissions of ammonia (NH3) and nitrous oxide (N2O) gases. In couple to the economic loss, such N losses may threaten atmospheric quality and results in poor plant synchrony. Application of both urease and nitrification inhibitors is encouraged as an approach to mitigate these gaseous losses. The rate of urea hydrolysis is accelerated as it remains in conventional form and about 70% of applied urea losses. Ammonia volatilization (NH3) is a substantial loss of urea. Therefore, to minimize NH3 volatilization and to supply the adequate Cu and Zn was the major aim of this research. Copper and Zn status were evaluated in selected paddy soils of Malaysia and Pakistan. Based on the results, Kuala Kedah and Chempaka soil series were below the critical level (Cu 0.1-1.0 mg kg-1 and Zn 0.5-3.0 mg kg-1) according to the method Mehlich-I in Malaysia, whereas in Pakistan Rustum soil series was below the critical level on Zn ( AB-DTPA 0.5 mg kg-1). Soils deficient in Cu and Zn were selected for this current study. The research was based on trials conducted at: (1) laboratory; (2) glass house; and (3) field conditions. Copper and Zn coated urea was prepared manually, where micronutrient fertilizer sources copper sulphate (3 and 5 kg ha-1) and zinc sulphate (7 and 10 kg ha-1) were used. Palm stearin was used as coating material to overlap Cu and Zn on urea. The specific aims of this study were to evaluate the effect of Cu and Zn coated urea on: (1) NH3 volatilization loss; (2) yield components of rice under acidic and alkaline soils; and (3) fluctuation of soil Eh and pH. In this regard a laboratory study was conducted on two acidic soil series of Malaysia. Results revealed that 50% less NH3 volatilization loss was observed under Cu and Zn coated urea treated soils as compared to common urea. After the positive results found in laboratory testing of Cu and Zn coated urea, a glass house study was designed to evaluate its effect on rice and Cu and Zn availability. Copper (3 and 5 kg ha-1) and Zn (7 and 10 kg ha-1) either alone or in combinations were applied as surface application or coated with urea followed by recommended doses of P and K (70 kg ha-1). Results manifested that Cu and Zn coated urea controlled fluctuating pH, Eh and facilitated Cu and Zn availability. The Cu and Zn had positive effect on growth, yield and nutrients concentration in rice plants. There was 40.9% yield increment over control under acidic soils. To confirm the results of glass house, a filed study was conducted on alkaline soils of Pakistan. Copper and Zn were applied all in coated form either alone or in the combinations (Cu3, Cu5, Zn10 and Zn15 kg ha-1) followed by the recommended doses of P (70 kg ha-1) and K (50 kg ha-1). Copper and Zn coated urea showed the positive response on the growth and yield of rice (50% grain yield increment was obtained over control). Coated urea increased the Cu, Zn and N contents in soil and plants.